2022
DOI: 10.3390/su142215048
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Digital Accounting System Usage on SMEs Performance: The Moderating Effect of COVID-19

Abstract: In the literature, studies have evidenced the efforts adopted by firms to develop digital technology with the hope of achieving sustainable decisions and competitive performance. However, studies have yet to provide an extensive explanation of the mechanisms used by firms in their digital technology adoption to impact and enhance value, particularly among small and medium enterprises (SMEs). In this regard, accounting information has served as a fundamental basis for business decision-making and the extensive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 48 publications
(37 citation statements)
references
References 81 publications
(178 reference statements)
0
14
0
Order By: Relevance
“…The D&M (2003) extension with the addition of decision making quality variables is useful in studying technologies and innovations, in various contexts and nations having similar level of backgrounds, both economic and social, ( Almaiah et al, 2022k ; Khassawneh & Lutfi, 2014 ). Nevertheless, the limited size of the sample employed in this study calls for caution when generalizing the results to other nations as suggested by past literature ( Almaiah et al, 2022l ; Lutfi et al, 2022c , 2022h , 2022i , Lutfi et al, 2022j ).…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…The D&M (2003) extension with the addition of decision making quality variables is useful in studying technologies and innovations, in various contexts and nations having similar level of backgrounds, both economic and social, ( Almaiah et al, 2022k ; Khassawneh & Lutfi, 2014 ). Nevertheless, the limited size of the sample employed in this study calls for caution when generalizing the results to other nations as suggested by past literature ( Almaiah et al, 2022l ; Lutfi et al, 2022c , 2022h , 2022i , Lutfi et al, 2022j ).…”
Section: Discussionmentioning
confidence: 93%
“…In an uncertain, information-requiring environment, the firm's information processing and sourcing play a key role and in this regard, using AIS can extend such capabilities, making the firm adept at the collection, analysis and relay of information, and enhancing the possibility of achieving optimum performance ( Lutfi et al, 2022k ).…”
Section: Discussionmentioning
confidence: 99%
“…Several IS adoption theories have been used in literature focusing on various dimensions at the organizational and individual levels. At the organizational level, DOI, which has formed the foundations for the expansion of several theoretical frameworks such as TOE [35,36], is the most popular and frequently employed framework for technological innovation [25,37]. Most of the IS frameworks are technologically oriented to explain technological characteristics which influence the adoption decisions [38].…”
Section: A Theoretical Foundationsmentioning
confidence: 99%
“…At the individual level, frameworks such as the theory of reasoned action (TRA) [41], technology acceptance model (TAM) [42], the theory of planned behavior (TPB) [43] and UTAUT are well-established for determining individual characteristics in IS adoptions [36]. TAM is a widespread framework to investigate IS adoptions such as cloud ERP [32,44].…”
Section: A Theoretical Foundationsmentioning
confidence: 99%
See 1 more Smart Citation